A GESTÃO ESTATAL BRASILEIRA : A PRIVATIZAÇÃO DO PÚBLICO E OS REBATIMENTOS NAS POLÍTICAS SOCIAIS - Luiz Vargas, Thais (Revista Serviço Social em Perspectiva, 2020)
The present work aims to analyze, from the Marxist tradition, the Brazilian state management in the scope of the Federal Public Administration, seeking to unveil the process of privatization of the public in the context of the neoliberal (managerial) State. It also aims at revealing how the relationship between what is a duty-power of the State and its administration in the performance of its tasks, its purposes, and what is the prerogative of civil society, or the individual, occurs, since they have been observed an expanded framework of the state’s lack of responsibility for the expressions of the social question. It is also intended to describe how in the days (of neoliberal conjuncture) the universal feature has given way to the focused character and the public provision yielding space to the private. At the end, the present study seeks to analyze the consequences of this theoretical, institutional (administrative) and political conflict for the definition of state public policies, especially the refutations in Brazilian social policies in a context of counterreforms.